Answer:
h(n) = 4h(n - 1) -2h(n - 2) + h(n - 3)
Step-by-step explanation:
Let d(n) be the number of good n character strings ending in 0
Let e(n) be the number of good n character strings ending in 1
Let f(n) be the number of good n character strings ending in 2
Let g(n) be the number of good n character strings ending in 3
h(n) = d(n) + e(n) + f(n) + g(n)
e(n) = g(n) = h(n - 1)
f(n) = d(n - 1) + f(n - 1) + g(n - 1)
d(n) = d(n - 1) + e(n - 1) + g(n - 1)
f(n) = h(n - 1) - e(n - 1) = h(n - 1) - h(n - 2)
d(n) = h(n - 1) - f(n - 1) = h(n - 1) - h(n - 2) + h(n - 3)
h(n) = 4h(n - 1) -2h(n - 2) + h(n - 3)
Checking recursion manually,
when h(1) ⇒ d(1) = 1, e(1) = 1, f(1) = 1, g(1) = 1, h(1) = 4
h(2) ⇒ d(2) = 3, e(2) = 4, f(2) = 3, g(2) = 4, h(2) = 14
h(3) ⇒ d(3) = 11, e(3) = 14, f(3) = 10, g(3) = 14, h(3) = 49
h(4) ⇒ d(4) = 39, e(4) = 49, f(4) = 35, g(4) = 49, h(4) = 172
Note:
Sum of the four values gives "h(n)
Since e(n) = g(n), the values are the same